Purple Sweet Potato Soft Bun as a Value-adding of Local Agricultural Production - Chuamsompong, Boonyaporn; Siripanwattana, Chanchana (Journal of Food Health and Bioenvironmental Science, 2023)
The research was undertaken to study the appropriate substituting level of purple sweet potato (PSP) flour for bread flour in making soft buns. Soft buns with 0-50% PSP flour substituting for bread flour were prepared. Prepared soft buns were visually observed and tests were performed to determined pH, moisture, color, firmness and springiness. A hedonic test was conducted with 30 untrained panelists in order to select the suitable level of PSP flour substitution. The original soft bun and the suitable PSP flour substituted soft bun were compared regarding shelf-life and nutritional values. When PSP flour substitutions were increased from 0 to 50%, visual observation of prepared soft buns showed size decreasing, crust color changed from light golden brown to dark purplish brown, crumb color changed from off white to dark purplish brown, texture was firmer, and springiness was lesser. The pH of the soft buns was 5.47 – 5.65, which were not significantly different. The moisture contents of the soft buns with 10 -50 % PSP flour substitution, 25.03-26.35 %, were significantly different and slightly higher than 24.49 % of the control sample (0% PSP flour substitution). The hedonic test showed that 30 % PSP flour substituted soft bun had the highest score (8.16) on overall liking. Therefore, it was selected as an appropriate soft bun for further study. The shelf-life of the control and 30% PSP flour substituted soft buns strored in polyvinylidenechloride (PVDC) bags with oxygen absorber, resulted in 3 days at room temperature (25 °C) and 7 days at refrigerator temperature (4 °C). Soft bun at 30 % PSP flour substitution had a noticeable increase in vitamin A (from 981.0 to 3105 µg), carotene (from 0.7 to 13.4 mg), vitamin E (from 5.5 to 11.9 mg) and potassium (from 520.4 to1093.4 mg) compared to original one. Commercial PSP soft bun production with 30% PSP flour substitution for bread flour could add value for the local agricultural produce.